TANGGAPAN PENONTON DI DAERAH KETAPANG KABUPATEN KOTAWARINGIN TIMUR KALIMANTAN TENGAH TERHADAP ACARA DOKUMENTER DUA DUNIA TRANS 7 - Hamdani Hamdani (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2017)
This research comes from an event titled Two World which is a show owned by Trans7. This event has a lot of religious messages through jinmelalui advice through the body of the mediator (genie penetrates into the human body) .The purpose of this study is to know the level of material understanding of the World Two Trans7 event based on existing categories of audience in Ketapang Kotawaringin East of Central Kalimantan against this Two World event. This research method is descriptive qualitative field research (field) in town in Middle Kalimantan region named Sampit and more specifically Ketapang Village area So with the data obtained, the authors conducted a questionnaire that has contained questions about the response to the World Two event in Trans7.In addition, also coupled with various manuals in theory to do this research. The results of this study can be seen that there are messages of da'wah in this event though many smells of mystic things. As for the religious message about belief (akidah), Worship (shariah) and Moral (akhlak). Also in the event Two World also, from the results of the question with the jinn is implied ban on begging to the deceased. Moreover, if to adore them. Remember that the dead only require prayer posts, not for worship. Those are some of the sage messages implied by the jinns' rantings in the Worlds Two show that aired on Trans7. Seeing some of the precious messages that have been conveyed by the Jinn, men should be ashamed for being nasehati by the people of the unseen world that is identical with the evil and sinister impression